Motivasi Kemandirian Anak Yatim dalam Dakwah: Analisis Kontekstual Surat An-Nisa Ayat 5 Berdasarkan Tadabbur Al-Qur'an Al-Karim oleh Prof. Dr. H. Zainal Arifin, Lc, MA - Sari, Fitri Meliya; Arifin, Zainal (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2022)
In Sura An-Nisa verse 5 teaches to motivate orphans to be trained to be independent in financial management in good language. Train so that the orphan and the mother can be independent, discard the mentally poor and become a great adult. In the management of orphans' property, the manager may take a reasonable wage, if the manager is poor and in need, but those who are capable are expected to exercise restraint. So that the entrusted property can become a living capital for orphans and families. According to the Qurt the yam in the fifth verse of Qualan ma'rufa in question is a word that is pleasant to the soul and makes it submissive and prevents the orphans' property from being wasted. In Islamic communication, motivating someone to work is a very good thing. When motivating based on islamic communication ethics, people will be passionate about working and have a good influence on that person.